Pengendalian Penyakit Mulut Dan Kuku Melalui Vaksinasi Massal Di Wilayah UPTD Suela Dan Wanasaba Lombok Timur - Lalu Hadian Hizri; Husniati; Faikatunnisa; Aufa marsadi Ishtibar; Asnawi (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Control of Foot and Mouth Disease through Mass Vaccination in the UPTD Suela and Wanasaba Areas, East Lombok, has been carried out. The service method was carried out by a participatory method between UPTD officers, the Faculty of Animal Husbandry University of Mataram, and cattle farmers in Suela and Wanasaba Districts, East Lombok. The service was carried out at the UPTD of Suela District, which consisted of two villages, namely Perigi Atas, Perigi Tengah, and UPTD Wanasaba District, which consisted of two villages, namely East Beririjarak and West Beririjarak. The results of the mass vaccination program were obtained that the involvement of farmers in cattle vaccination at UPTD Suela was 17 people with the number of cows vaccinated as many as 75 cows. Meanwhile, in UPTD Wanasaba District, the involvement of farmers reached 27 farmers with the number of cows vaccinated as many as 82 cows. The total number of cows vaccinated during the program was 157 heads or 82% of the cattle population in the two UPTDs. The mass vaccination program went well, no cows experienced symptoms of illness after 2 weeks of vaccination. The conclusion of the activity, the mass vaccination program to prevent the transmission of foot and mouth disease at UPTD Suela and Wanasaba was successful. For two weeks after the vaccination of the cattle farmers group, no one showed symptoms of illness.